Konstruksi Hukum Hakim Mengabulkan Gugatan Penggugat atas Keputusan Tata Usaha Negara Studi Putusan Pengadilan TUN Banjarmasin No.04/G/2011/PTUN.BJM - Yuka Destralanda; Dr. Soehartono, S.H., M.Hum - (Sebelas Maret University, 2019)
State administrative courts is a judicial committee having authority to give justice to people who have problem in state administration. The dispute on state administration is dispute in state administration between two person or civil law legal entity and the offcial. One of the most interesting dispute to be discussed is a dispute about Prof. Dr. Ir. H. Udiansyah MS who has been stopped for his position in University of Lambung Mangkurat which is stated in Rector letter no.052/H8/KP/2011 and no.058/H8/KP/2011. This research approach was casuistic to analyze the conception of the judge verdict for this dispute. Beside that, this research used normative approach to saw the construction of the law on the verdict. The result of this research is used in law explanation as an input for judgement system in the future. The data which is used was the verdicts from the dispute and the expert statement to explain the construction of the verdict with its rationalization. The judge has granted the suit for Unlam Rector No.052/H8/KP/2011 and No.058/H8/KP/2011 based on the rationalization the defendants as the offcial never give the legal certainty and had violate the right administration system which causing irregularity, imbalance, and problem in state administration and injustice for the plaintiff.Keywords: state administrative courts, Verdict Conception, Verdict on stopping as offcial.